How Positive and Negative Emotions Promote Ritualistic Consumption Through Different Mechanisms - Song, Wei; Zhao, Taiyang; Huang, Ershuai; Liu, Wei (Frontiers in Psychology, 2022)
Ritualistic consumption refers to integrating ritual elements into the process of product design and usage. By conducting three studies, we find that ritualistic consumption can offer new and interesting experiences and help consumers gain a sense of control. Both positive and negative emotions can promote ritualistic consumption tendencies. However, their underlying psychological mechanisms are different. Specifically, positive emotion can arouse consumers’ desire for interesting experience and thus promotes their preference for ritualistic consumption, while negative emotion can arouse consumers’ need for control and thus promote their preference for ritualistic consumption. Our research results offer a theoretical contribution and practical inspiration for emotional marketing.